WORK-FAMILY CONFLICT, JOB ENGAGEMENT, EMOTIONAL EXHAUSTION: THEIR INFLUENCE ON THE TURNOVER INTENTION OF INDIGENOUS PAPUAN FEMALE EMPLOYEES - Noermijati, Noermijati; Wongviboonrath, Suratchanee; Itlay, Wiwin; Sudiro, Achmad (Universitas Brawijaya, Indonesia, 2020)
This study presents a model linking work-family conflict (WFC), job engagement, emotional exhaustion, and turnover intention. The primary objective was to investigate the direct effect of work-family conflict on turnover intention and its indirect effect through job engagement and emotional exhaustion. The data were obtained by a questionnaire from a sample of 111 respondents of Papuan Female who work at PT Freeport Indonesia. Data analyzed by used structural equation modeling with PLS-based and found two insignificant paths in models. The result showed that WFC hasa significant effect in improving turnover intention and emotional exhaustion, but have no significant effect in lowering job engagement. Moreover, job engagement does not significantly effect in lowering turnover intention, while emotional exhaustion has a significant effect in increasing job engagement and turnover intention. The mediation test results indicated that job engagement cannot provide an important role, both in the work-family conflict effect on turnover intention, and emotional exhaustion effect on turnover intention. Instead, emotional exhaustion can provide a partial mediating role in the work-family conflict effect on turnover intention, in which this path is one of the important findings with practical implications and the consequences of these findings for future research are further discussed.